anonymous
  • anonymous
solve the equation ln(X-3)=ln(X+2)+3 how do you cancel ln. I know when you have log you can do this= log base 5 (2X+4)=3
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
katieb
  • katieb
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
Just a start and i'm not definitive on this but can you do ln( (x-3)/(x+2) ) = 3 as subtracting logs equates to dividing them as one 'ln'.
TuringTest
  • TuringTest
^that is correct then raise e to the power of both sides...
anonymous
  • anonymous
can you help on this problem, Ln(x-3)=Ln(x+2)+3 please! so i can see it? how you do it

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

TuringTest
  • TuringTest
As is stated above remember the log rule\[\log a-\log b=\log(\frac ab)\]so here we can do the following:\[\ln(x-3)=\ln(x+2)+3\]\[\ln(\frac{x-3}{x+2})=3\]now raise e to the power of both sides and isolate x:\[\frac{x-3}{x+2}=e^3\]\[x-3=e^3x+2e^3\]\[x-e^3x=3+2e^3\]\[x(1-e^3)=3+2e^3\]\[x=\frac{3+2e^3}{1-e^3}\]please pay try to follow how I did this so you can do the problems yourself in the future.
TuringTest
  • TuringTest
please try*
anonymous
  • anonymous
awesome!! thx you yes, i will try myself so i can be ready for my test, right practice take perfection.thank you so much!
TuringTest
  • TuringTest
welcome!
anonymous
  • anonymous
LnX+Ln(X+2)=2 this is what i did Ln(X+0)/(X+2)=2 (X+0)/(X+2)=e^2 x+=e^2X+2e^2 x+e^2-x=-0+2e^2 x=2e^2/x+e^2= the calculator says error cause i can not divide by o, off course, but my professor book answer is x=1.896 or x=-3.896 what iam doing wrong?
TuringTest
  • TuringTest
you have a slightly different rule applying with addition\[\log a+\log b=\log(ab)\]so here you have\[\ln x+\ln(x+2)=\ln(x^2+2x)\]try to take it from there
TuringTest
  • TuringTest
...and you never need to add a zero like that. No point in it.
TuringTest
  • TuringTest
Basic log rules:\[\log a+\log b=\log(ab)\]\[\log a-\log b=\log(\frac ab)\]\[\log(x^a)=a\log x\]\[\log_b x=\frac{\log_a x}{\log_a b}\]these are your best friends for these kind of problems.
anonymous
  • anonymous
so, Ln x cancel and just end up with(x+2)/(x^2+2x)?
anonymous
  • anonymous
oh.. did you multiple (x).(x+2) and end up x^2+2x-2=0 and from then do the quadratic formula?
TuringTest
  • TuringTest
\[\ln x+\ln(x+2)=2\]\[\ln(x^2+2x)=2\]\[x^2+2x=e^2\]\[x^2+2x-e^2=0\]now you can use the quadratic formula.
anonymous
  • anonymous
thx! how about this problem e^x=35
anonymous
  • anonymous
Take ln of both sides as ln undoes e^x.. so: ln(e^x) = ln(35) x = ln(35)
anonymous
  • anonymous
oh i was doing e^35 iam a little confused i though the ln cancel in both sides
anonymous
  • anonymous
how would you do this problem 2^3x=16 i know base is 2
anonymous
  • anonymous
I'm not 100% sure but if you take log(base 2) on both sides you get 3x = 4 hence x = 4/3 is that correct?
anonymous
  • anonymous
no, is 2 to the power of 3x=16
anonymous
  • anonymous
2^3x=16
anonymous
  • anonymous
yeah, that's what I did - solve that for x which gives you 4/3. type log base 2 (16) into your calculator and you'll get 4. hence 3x = 4
anonymous
  • anonymous
ah.. thx! what the formula for that problem?
anonymous
  • anonymous
None - just knowing the rules of logarithms.
anonymous
  • anonymous
i started this problem original problem is 5e^4x=500 so what i did is the following:5/5 e^4x=500/5 e^4x=e^100 4x=4.60517-4 -4x x=.60517?
anonymous
  • anonymous
Chances are that's incorrect as answers rarely come out like that. I think this is correct: e^4x = 500/5 e^4x = 100 ln(e^4x) = ln(100) 4x = ln(100) x = ln(25) <-- always leave your answer in terms on ln as it is more precise than a decimal.
anonymous
  • anonymous
I've made a mistake again.. I'm getting tired: x = ln(100) / 4
anonymous
  • anonymous
I understand you been tired, I been home work since 11a.m i shall also take a break. thank you so much for you help i really
anonymous
  • anonymous
No worries.

Looking for something else?

Not the answer you are looking for? Search for more explanations.